Estimating the time required to reach HPV vaccination targets across Europe - Ilias Gountas; Mohammed Aman; Deepak Alexander; Robert Hughes; Georgie Weston; Ugne Sabale (Taylor & Francis Group, 2024)
Background Cervical cancer (CC) is one of the most common causes of cancer-related deaths in women. The World Health Organization (WHO) has called for the CC elimination as a public health priority and has urged countries to achieve a 90% vaccine coverage rate of human papilloma virus (HPV) vaccination among 15-year-old girls by 2030.Research design and methods Regression models were fitted to the WHO HPV vaccine coverage rate data to estimate when the 90% vaccine coverage rate target would be achieved in 22 European countries.Results The mean vaccine coverage rate of included countries was 62.2% (SD: 18.3). Nine countries (Iceland, Norway, Portugal, Ireland, Hungary, Spain, Sweden, Denmark, and Switzerland) are expected to achieve a 90% vaccine coverage rate by 2030. Six countries (Estonia, Cyprus, Netherlands, France, Germany, and Italy) are expected to reach a 90% vaccine coverage rate between 2030 and 2040 whereas seven countries (Belgium, Bulgaria, Finland, Latvia, Luxembourg, Malta, and Slovenia) are not expected to achieve the 90% vaccine coverage rate target by 2040.Conclusion The majority of European countries are not on track to achieve 90% vaccine coverage rate by 2030. To achieve this, a significant increase in the annual vaccine coverage rate growth rate is required.